PENGARUH KUALITAS LAYANAN PEMBUKAAN REKENING ONLINE PADA APLIKASI MOBILE BANKING TERHADAP KEPUASAN NASABAH: (Studi Kasus Bank Syariah Indonesia KC Kota Pekanbaru Sudirman 2) - Hanifah Rosanah; Muhammad Lisman (JURNAL ISLAMIKA, 2022)
This study aims to determine the effect of online account opening service quality in the mobile banking application on customer satisfaction at Bank Syariah Indonesia KC Pekanbaru City Sudirman 2. This research method uses quantitative methods and data collection techniques are carried out by distributing questionnaires to 97 respondents, namely customers of Bank Syariah Indonesia KC City of Pekanbaru Sudirman 2. Based on the results of the t test, the tcount value is 12.631 > ttable 1.985 and the significance value of the Quality of Online Account Opening Service variable (X) on Customer Satisfaction (Y) is 0.000 <0.05, which means a positive and significant influence between the variables Quality of Service Opening an online account on Customer Satisfaction. With the results of the coefficient of determination test (R2) of 62.7%.